Simulacre et modernité : l’illusion d’optique dans On the Western Circuit de Thomas Hardy - Catherine Lanone (Cahiers Victoriens et Edouardiens)
This paper focuses on various visual devices which Thomas Hardy chooses to include in his short stories in order to question the Victorian cult of progress, such as photographs, the Crystal Palace or more unexpectedly the phenakistiscope, which clearly lies behind the obsessional description of the « steam circus » in the short story entitled On the Western Circuit. Although Hardy was forced to bowdlerize his text, removing allusions to sexual intercourse and subsequent pregnancy, the real shock lies less in the hackneyed sentimentality of the illegitimate baby theme than in the depiction of modernity and modern exchanges — or systems of communication through trains, letters, or judicial rounds — as vicious circles breeding spurious desires and fantasies. The novel displays the enticing flickering sparks of desire created by the new wheel of fortune, turning the steam circus into a metaphor of ruthless mutations and hopelessly warped human relationships.